2022
DOI: 10.3390/ma15030723
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Performance of Bituminous Mixture Using 100% Content RAP with Bio-Rejuvenated Additive (BRA)

Abstract: The low RAP content, hot mixing conditions, and the addition of a high ratio of new bitumen and aggregates result in low economic and environmental benefits for current regeneration technologies. A bio-rejuvenated additive (BRA) that can fully (100%) regenerate the RAP without heating is proposed in this paper. To reveal the mechanisms of BRA-rejuvenated RAP, the effects of BRA on the chemical structure and molecular weight of the RAP were investigated using Fourier-transform infrared spectroscopy and gel perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…It can be seen from Fig. 4 that the main functional groups of the three kinds of paints are as follows: the double peaks near 2900 cm − 1 are caused by the antisymmetric and symmetric stretching vibration of alkane CH 2 and its derivatives, indicating that there are more long-chain alkanes in the paint; 1440 cm − 1 is the absorption peak superposed by CH 2 bending vibration and CH 3 asymmetric bending vibration of alkanes; 870 cm − 1 is the absorption peak caused by the out of plane bending vibration of benzene aromatic CH; 720 cm − 1 is the absorption peak caused by the plane swing of alkane CH 2 [32]. Compared with the original paint, the 5% T and 5% T + A pastes have increased three obvious infrared absorption peaks of 1740 cm − 1 , 1240 cm − 1 and 1020 cm − 1 .…”
Section: Chemical Compositionmentioning
confidence: 99%
“…It can be seen from Fig. 4 that the main functional groups of the three kinds of paints are as follows: the double peaks near 2900 cm − 1 are caused by the antisymmetric and symmetric stretching vibration of alkane CH 2 and its derivatives, indicating that there are more long-chain alkanes in the paint; 1440 cm − 1 is the absorption peak superposed by CH 2 bending vibration and CH 3 asymmetric bending vibration of alkanes; 870 cm − 1 is the absorption peak caused by the out of plane bending vibration of benzene aromatic CH; 720 cm − 1 is the absorption peak caused by the plane swing of alkane CH 2 [32]. Compared with the original paint, the 5% T and 5% T + A pastes have increased three obvious infrared absorption peaks of 1740 cm − 1 , 1240 cm − 1 and 1020 cm − 1 .…”
Section: Chemical Compositionmentioning
confidence: 99%
“…The main waste polymer products are polyethylene (PE) [3], polyvinyl chloride, polyethylene terephthalate, ethylene vinyl acetate copolymer [10], etc. Recycled polyethylene (RPE)-based plastics melt at about 150 • C [11], have better low-temperature properties [12,13], and are one of the most suitable waste plastics for use as asphalt modifiers [14]. Alghrafy et al [15] investigated the influence of RPE on the rheology and fatigue properties of modified asphalt and concluded that asphalt made from RPE has better resistance to rutting and fatigue cracking after hardening.…”
Section: Introductionmentioning
confidence: 99%
“…Some approaches to characterize and classify the RAP were applied to promote its popularization and utilization [ 17 ]. Chen et al investigated the mechanism and performance of mixtures with 100% dosage RAP and bio-rejuvenated additive (BRA) and found that BRA restores the balance of the components of aged bitumen and elevate mechanical performance of asphalt mixtures [ 18 ]. Similar studies had also been reported by Zaumanis et al [ 19 ].…”
Section: Introductionmentioning
confidence: 99%